Solutions handbook for PC programmers - Sanchez, Julio (J. Ranade workstation series., 1996)
This work, intended to be of use to PC programmers, software engineers and computer science students, provides a problem solver for common programming problems. It includes chapters on sound programming and CD-ROM programming, and has special emphasis on VGA and SuperVGA graphics.